The Big Picture: Designing Long-term Contributions in the Arts and Humanities - Ward, Julie Ann (My University, 2022)
The Big Picture: Designing Long-term Contributions in the Arts and Humanities is a series of seven, interconnected workshops. It was designed to be completed sequentially by a cohort of junior faculty in the arts and humanities, although each session could be useful as a standalone workshop, depending on your specific goals. It draws on various inspirations, including Julia Cameron’s The Artist's Way, Maggie Berg and Barbara K. Seeber’s The Slow Professor, Paul J. Meyer’s “Wheel of Life” coaching tool, and techniques shared by teachers like Susan Drouilhet and Matt Bell. This annotated handbook includes: • A facilitator’s guide with step-by-step instructions for coordinating each session • Annotations with responses from both me (the author) and the participants of the pilot program at the University of Oklahoma, 2021-2022 • Examples of participant responses to the various activities
This guide will be useful to your group if: • You would like to support interdisciplinary relationships between arts and humanities scholars at your institution; • You would like to encourage faculty to think beyond the tenure clock and focus on their contributions to their field and society; and • You would like to acknowledge the fullness of faculty life, which includes family, physical and mental health, friendships, leisure time, creative pursuits, political commitments, and financial needs in addition to scholarly work. The workshop series can be completed virtually or in person; groups can meet once a week or once a month, or daily in an intensive 7-day retreat; it can be facilitated by a designated coordinator or participants can take turns leading the sessions according to this guide. The session guides include time suggestions for a two-hour session – you can adjust according to your own needs. All you need is a group willing to commit to the whole series and a time and place that is convenient for you. The materials required for each session are minimal and are listed at the top of each session guide. Each participant will need a copy of The Slow Professor by Maggie Berg and Barbara K. Seeber.